Sistem Informasi Manajemen Penjadwalan Penggunaan Laboratorium Pada Poltekkes Kemenkes Jambi - Warsono, Warsono; Mulyono, Herry (Jurnal Manajemen Sistem Informasi, 2022)
Poltekkes Kemenkes Jambi is organizing health education programs which consists of 14 study programs under 7 departments representing the health profession. in the process of scheduling the use of laboratories is based on active lectures in the current semester. The head of the study program makes a draft schedule and it will be agreed on its use at the lesson preparation meeting. The problem faced was that during the learning preparation meeting there were many schedule adjustments due to conflicting laboratory use, this was due to the absence of real-time references during the scheduling drafting process. The purpose of this study is to overcome this problem by designing a laboratory scheduling management information system that provides a real time reference of schedule drafts from other study programs, so that scheduling of laboratory use both within the department and between departments can be carried out more effectively and efficiently. The flow of this research starts from problem identification, literature study, data collection, system analysis, system design and making research reports. This research produces a prototype of a laboratory scheduling management information system designed to optimize the laboratory use scheduling process at the Poltekkes Kemenkes Jambi based on current business processes. It is expected that the Poltekkes Kemenkes Jambi can apply the results of this research by developing it into an information system.